1979
DOI: 10.1210/jcem-49-6-847
|View full text |Cite
|
Sign up to set email alerts
|

Is Human Decidua a Specialized Endocrine Organ?*

Abstract: The production of protein hormones by human placenta, amnion, chorion, and decidua capsularis was studied in in vitro experiments to establish whether the decidua could be considered a specialized structure for the release of PRL. The tissues were incubated in the incubation medium, we found a highly significant rise of PRL during culture of the decidua, while no increase was noticed during culture of the placenta or amnion. Conversely, chorionic somatomammotropin and CG increased greatly and quickly during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

1982
1982
1985
1985

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 5 publications
3
23
0
Order By: Relevance
“…Our explant culture system for human decidual tissues was shown to be a good experimental model for studying the production of IR-PRL, but the larger amounts of IR-PRL release in the incubation medium for the first 24 hour interval may have been due to a contamination factor, such as a contamination by adherent maternal serum and/or amniotic fluid. A similar high rate of IR-PRL release was observed by Bigazzi et al (Bigazzi et al, 1979). Because our explant culture system for human decidual tissues is patent for a period of several days, it seems to be very effective in excluding contamination from both short-term and long-term culures.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our explant culture system for human decidual tissues was shown to be a good experimental model for studying the production of IR-PRL, but the larger amounts of IR-PRL release in the incubation medium for the first 24 hour interval may have been due to a contamination factor, such as a contamination by adherent maternal serum and/or amniotic fluid. A similar high rate of IR-PRL release was observed by Bigazzi et al (Bigazzi et al, 1979). Because our explant culture system for human decidual tissues is patent for a period of several days, it seems to be very effective in excluding contamination from both short-term and long-term culures.…”
Section: Discussionsupporting
confidence: 83%
“…Japon. FebruaryFurthermore, it was also revealed that the decidual tissues thus obtained constantly produced and secreted IR-PRL in the incubation medium in a considerably high amount even as compared with those previously reported (Golander et al, 1978;Bigazzi et al, 1979;Richards et al, 1982) and that the variation from specimen to specimen was so small as to make it possible to compare the production of IR-PRL by the decidual tissues under various conditions. Radioimmunoassay of PRL IR-PRL was measured in the incubation medium and in the supernatant of the tissue homogenate to assess the initial content in the tissues and its release in the incubation medium by using a PRL-RIA-KIT (PRL Kit, Daiichi).…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Furthermore, it has been reported that PRL production in deciduous tissue cultures is not controlled by dopamine, and in particular, it is unaffected by BC. Thus, even when BC treatment continued to term, yielding low fetal and maternal blood PRL levels, amniotic fluid levels remain normal [15][16][17], There is a second theoretical risk: a possible effect of depressed maternal dopamine levels upon fetal development, e.g. in macroPROL not treated or treated for less than 4 weeks; this has not been considered, except during the first weeks of pregnancy [18].…”
Section: Discussionmentioning
confidence: 99%